FTO genetic variants and risk of obesity and type 2 diabetes: a meta-analysis of 28,394 Indians. - Vasan, S; Karpe, F; Gu, H; Brismar, K; Fall, C; Ingelsson, E; Fall, T (2014)
OBJECTIVE: To investigate the magnitude of association of FTO variants with obesity, type 2 diabetes (T2DM), and related traits among Asian Indians. METHODS: Random-effect meta-analysis was performed on pooled data from eight studies (n = 28,394) for obesity and related traits and six studies (n = 24,987) for assessment of T2DM risk in Indians where FTO variants were reported. RESULTS: The minor A-allele of the FTO variant rs9939609 was associated with increased risk of obesity (OR 1.15, 95% CI 1.08-1.21, p = 2.14 × 10(-) (5) ), BMI (β = 0.30 kg/m2, 95% CI 0.21-0.38, p = 4.78 × 10(-) (11) ) and other regional adiposity measurements [waist (β = 0.74 cm, 95% CI 0.49-0.99), HC (β = 0.52, 95% CI 0.26-0.78), and waist-hip ratio (WHR) (β = 0.002, 95% CI 0.001-0.004)] in Indians (p ≤ 0.001). An increased risk for T2DM (OR 1.11; 95% CI 1.04-1.19, p = 0.002) was observed, which attenuated when adjusted for age, gender, and BMI (OR 1.09; 95%CI 1.02-1.16, p = 0.01). CONCLUSIONS: Our study provides evidence of association between common FTO variant and obesity risk among Indians with comparable effect sizes as in Caucasians. The attenuation of FTO-T2DM risk on BMI adjustment reinforces that BMI does not fully account for the adiposity effects among Asian Indians who are more centrally obese.